Development And Validation Of Rp-Hplc Method For Simultaneous Estimation Of Dapagliflozin And Saxagliptin In Bulk As Per Ich - Menasinakai, Akshata; Ronad, PM; Ankalikar, Aryaa; Chakraborthy, Gunosindhu; Rohilla, Seema; Maddi, Ramaiah; Mittal, Stuti; Ghosh, Souptik (Journal of Neonatal Surgery, 2025)
In the present work, a rapid, specific, accurate and precise reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed and validated for simultaneous determination of Dapagliflozin and Saxagliptin in bulk and pharmaceutical dosage form. Successful chromatographic separation of Dapagliflozin (DGN) and Saxagliptin (SGN) was carried out with altima C18 column (150 ×4.6 mm, 5 μm) with mobile phase consisted of a mixture of Acetonitrile and Potassium dihyrogen phosphate buffer in the ratio of 35:65 v/v and the pH of the buffer was adjusted to 5.5, delivered at a flow rate of 1.0 ml/min. The eluents are monitored by PDA detector and peaks values were measured at 225 nm. The retention times for DGN and SGN were 2.953 min and 2.209 min respectively. The present analytical method was validated according to ICH guidelines (ICH, Q2 R1). The linearity study of DGN and SGN was found in the concentration range of 10-50 μg/ml for both and coefficient of variance was 0.997 and 0.998 respectively. % recovery was found to be 100.19% and 99.81 % for DGN and Saxagliptin respectively. LOD was 1.10 μg/ml and 1.18 μg/ml and LOQ was 3.01 μg/ml and 3.12 μg/ml for DGN and SGN respectively. It inferred that the developed method was successfully applied for the simultaneous estimation of DGN and SGN in bulk and could be used for the routine analysis of the studied drugs in quality control laboratories.